Guarda compartilhada como expressão do princípio constitucional do melhor interesse da criança - Messias, Patricia Melo (2006)
The problem of custody of children is demanded when the parents, due to separation of spouses or judicial separation, or in the dissolution hypothesis of the consensual marriage, do not live in the same house or in the cases where the parents never cohabited. Granting to the children the fundamental right to live in family, the custody should always take into consideration the welfare of the minor, which is to have the presence of both parents in his life. The jointed custody is the familiar arrangement which gives continuity to the affective boundaries established between the father and the mother, even after the family transformation. The Constitucional Grounds of the jointed custody are the equality principle of genus, of the best interest for the minor and the absolute priority for the child and adolescent. It can be executed with or without housing alternating. The problems faced in its applicability by the parents do not impede its implementation. The jointed custody gives advantages to everybody involved: the parents, children and the judiciary, and finds in the mediation the way to its effectiveness, since it promotes the family participation in the litigation involvement. In spite of the acceptance of this modality of juridical arrangement in the Brazilian juridical ordering, it is still being constructed its acceptance gradually and culture, on the contrary what happens in the compared law, where it is applied frequently. An empirical research proved its operation and necessity that the parents are informed by the law representatives about the existence and advantages of the jointed custody.